Circ_0070203 Promotes Epithelial-mesenchymal Transition in Ovarian Serous Cystadenocarcinoma through miR-370-3p/TGFβR2 Axis - Tang, Qiong; Wen, Huiting; Hu, Haoyue; Chen, Xiaoli; Xu, Shuxiu; Fan, Li; Liu, Longyang; Li, Jing (Recent Patents on Anti-Cancer Drug Discovery, 2024)
Introduction: Circular RNAs (circRNAs) are important biological molecules associated with the pathogenesis of multiple cancers.Objective: This work aimed to investigate the function and molecular mechanism of circ_0070203 in high-grade serous ovarian cystadenocarcinoma (HGSOC).Methods: circRNA microarray was conducted to detect the circ_0070203 expression in HGSOC tissues. Bioinformatics analysis was used to find the binding sites between circ_0070203, miR- 370-3p and TGFβR2. Real-time quantitative reverse transcription PCR (RT-qPCR) was executed to detect the expressions of circ_0070203, miR-370-3p and TGFβR2 in HGSOC tissues and SKOV3 cells. Dual-luciferase reporter gene assay was used to validate the relationships between miR-370-3p and circ_0070203 or TGFβR2. Besides, transwell assays were conducted to assess the migrative, invasive abilities of ovarian cancer (OC) cells. Western blotting was adopted to detect the expression of epithelial-mesenchymal transition (EMT)-related proteins. The related patents were also studied during the research.Results: Circ_0070203 and TGFβR2 were upregulated, while miR-370-3p was downregulated in FIGO stage III-IV HGSOC tissues and SKOV-3 cell lines. circ_0070203 overexpression changed the expression of other EMT-related proteins and enhanced the migrative, invasive abilities of OC cells, while silencing circ_0070203 worked oppositely. Mechanistically, circ_0070203 could upregulate TGFβR2 expression in OC cells via sponging miR-370-3p.Conclusion: Circ_0070203 could promote the epithelial-mesenchymal transition, invasion, and metastasis of HGSOC via regulating the miR-370-3p/TGFβR2 axis. Our findings provided a potential biomarker for HGSOC therapy.
Keywords: epithelial-mesenchymal transition